2018
DOI: 10.1097/md.0000000000012606
|View full text |Cite
|
Sign up to set email alerts
|

Associations of race, mechanism of injury, and neighborhood poverty with in-hospital mortality from trauma

Abstract: Health disparities based on race and socioeconomic status are a serious problem in the US health care system, but disparities in outcomes related to traumatic injury have received relatively little attention in the research literature.This study uses data from the State Inpatient Database for Michigan including all trauma-related hospital admissions in the period from 2006 to 2014 in the Detroit metropolitan area (N = 407,553) to examine the relationship between race (White N = 232,109; African American N = 86… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 29 publications
1
20
3
Order By: Relevance
“…Demographic factors positively associated with survival included age group (16–64) (compared to age ≥ 65) and female gender. This differs from previous studies [ 5 , 18 , 21 ] where no similar associations were reported. Patients in the younger age are usually expected to have better odds of survival because of lower comorbidities.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Demographic factors positively associated with survival included age group (16–64) (compared to age ≥ 65) and female gender. This differs from previous studies [ 5 , 18 , 21 ] where no similar associations were reported. Patients in the younger age are usually expected to have better odds of survival because of lower comorbidities.…”
Section: Discussioncontrasting
confidence: 99%
“…The available literature reports contradicting findings on financial coverage and association with survival in trauma patients. Greene et al concluded that insurance status was a predictor of outcome with uninsured patients being at higher risk of death in both blunt and penetrating trauma [ 34 ] while Lober et al [ 21 ] noted better survival in patients with no insurance coverage attributing this finding to potentially larger proportion of healthy patients in the uninsured group. In this study of traumatic arrests any insurance status (compared to uninsured) was associated with improved outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…This differs from previous studies 5,16,19 where no similar associations were reported. Patients in the younger age are usually expected to have better odds of survival because of lower comorbidities.…”
Section: Discussioncontrasting
confidence: 99%
“…The available literature reports contradicting ndings on nancial coverage and association with survival in trauma patients. Greene et al concluded that insurance status was a predictor of outcome with uninsured patients being at higher risk of death in both blunt and penetrating trauma 34 while Lober et al noted a better survival in patients with no insurance coverage 19 attributing this nding to potentially larger proportion of healthy patients in the uninsured group. In this study of traumatic arrests any insurance status (compared to uninsured) was associated with improved outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Health disparities in outcomes for race and sex have been identified throughout medicine. [1][2][3][4][5][6] Although life expectancy gaps have improved over time, between 2016 and 2017, black Americans had a life expectancy of about 3.5 years less than white Americans. 7 Additionally, in 2018, men had a life expectancy of approximately 5 years less than women in the United States.…”
Section: Introductionmentioning
confidence: 99%